AmtDB: a database of ancient human mitochondrial genomes. Issue Volume 47:Issue D1(2019) (24th September 2018) - Ehler, Edvard; Novotný, Jiří; Juras, Anna; Chyleński, Maciej; Moravčík, Ondřej; Pačes, Jan
Abstract: Ancient mitochondrial DNA is used for tracing human past demographic events due to its population-level variability. The number of published ancient mitochondrial genomes has increased in recent years, alongside with the development of high-throughput sequencing and capture enrichment methods. Here, we present AmtDB, the first database of ancient human mitochondrial genomes. Release version contains 1107 hand-curated ancient samples, freely accessible for download, together with the individual descriptors, including geographic location, radiocarbon dating, and archaeological culture affiliation. The database also features an interactive map for sample location visualization. AmtDB is a key platform for ancient population genetic studies and is available athttps://amtdb.org .